Support of Economic Transition of Eastern European Countries by the European Bank for Reconstruction and Development - Hanna Dumała (Facta Simonidis)
Eastern European countries (Armenia, Azerbaijan, Belarus, Georgia, Moldova, Russia and Ukraine) receive financial and technical support among others from the European Bank for Reconstruction and Development in the process of its economic transformation. The article presents the value of support granted since 1991 for the whole region and individual countries, as well as the assessment of the projects co-financed by the Bank in terms of the „transition impact”. Eastern Europe remains the leader in terms of the amount of financial assistance received, but this does not reflect into a assessment of the progress of the transformation process: only two states in the region (Russia and Ukraine) have intermediate status and the remaining are still classified as early transition countries.